Fast H isotope and impurity mixing in ion-temperature-gradient turbulence. (2nd July 2018) - Bourdelle, C.; Camenen, Y.; Citrin, J.; Marin, M.; Casson, F.J.; Koechl, F.; Maslov, M.
Abstract: In ion-temperature-gradient (ITG) driven turbulence, the resonance condition leads to ion particle turbulent transport coefficients significantly larger than electron particle turbulent transport coefficients. This is shown in nonlinear gyrokinetic simulations and explained by an analytical quasilinear model. It is then illustrated by JETTO-QuaLiKiz integrated modelling. Large ion particle transport coefficients implies that the ion density profiles are uncorrelated to the corresponding ion source, allowing peaked isotope density profiles even in the absence of core source. This also implies no strong core accumulation of He ash. Furthermore, the relaxation time of the individual ion profiles in a multi-species plasma can be significantly faster than the total density profile relaxation time which is constrained by the electrons. This leads to fast isotope mixing and fast impurity transport in ITG regimes. In trapped-electron-mode (TEM) turbulence, in presence of electron heating about twice the ion heating, the situation is the inverse: ion particle turbulent transport coefficients are smaller than their electron counterpart.